The role of dogs in the relationship between telework and performance via affect: A moderated moderated mediation analysis - Junça Silva, A.; Almeida, M.; Gomes, C. (Animals, 2022)
Although there is evidence that pets may help individuals facing significant daily stressors, and that they may enhance the well-being of their owners, little is known about the benefits of pets for job performance. Since the COVID-19 pandemic crisis, teleworking was a strategy implemented in many countries to reduce the virus widespread and to assure organizational productivity. Those who work from home and who own pets may work close to them. Based on the conservation of resources theory, this study aimed to analyze whether positive affect mediated the relationship between telecommuting and self-reported job performance and if psychological and physical closeness to the pet would moderate this relationship in such a way that it would be stronger for those who worked closer to their pet, and who were more emotionally attached to them. For this study, we collected data from 81 teleworkers who did not own pets, and from 320 teleworkers who owned pets. Both answered an online questionnaire. Findings: Results from the study showed the existence of significant differences between those who owned and who did not own pets regarding positive affect and performance, in which those who owned pets reported higher levels of positive affect and self-reported performance and perceived telework more positively. Moreover, positive affect mediated the relationship between telework and self-reported job performance. Furthermore, emotional and physical closeness moderated the mediating effect. This study contributes to a better understanding of the human-animal interaction and how pets can be a personal resource able to change their owners’ affective experiences and job performance while they are working from home. The findings demonstrate that telework may be a suitable organizational strategy for pet-owners.